Cooperative effects of slight acidic electrolyzed water combined with calcium sources on tissue calcium content, quality attributes, and bioactive compounds of 'Jiancui' jujube. (7th November 2019) - Li, Xiaojuan; Zhi, Huanhuan; Li, Meng; Liu, Qiqi; Xu, Juan; Dong, Yu
Abstract: BACKGROUND: Slight acidic electrolyzed water (SAEW) has been widely used in cleaning systems of fruit and vegetables. It strongly reduces microbial contamination. However, no information is available on whether SAEW offers the potential for fresh jujube cleaning. The purposes of this study were, first, to compare the effectiveness of SAEW with commercial sanitizers (i.e. sodium hypochlorite (NaClO) or calcium hypochlorite (Ca(ClO)2 )) on 'Jiancui' jujube; second, to determine the response of fruit decay, tissue calcium (Ca) content, and quality attributes to dip application of calcium nitrate (Ca(NO3 )2 ) by concentration; and third, to investigate the effects of SAEW combined with Ca(NO3 )2 or calcium acetate (Ca(OAc)2 )) on fruit Ca uptake, quality attributes, and bioactive compounds. RESULTS: Fruits washed with NaClO, Ca(ClO)2, or an SAEW solution showed no difference in reduction of decay incidence. In contrast to NaClO treatment, SAEW or Ca(ClO)2 significantly retarded losses in fruit firmness (FF), green color (hue angle), and skin lightness ( L *), and maintained intact pericarp tissue structure during storage at 1 °C. Application of Ca(NO3 )2 at 5–10 g L −1 effectively promoted Ca 2+ uptake and minimized declines in FF and L * value but had no effect on decay development. Adding 10 g L −1 Ca(NO3 )2 or Ca(OAc)2 to SAEW provided an additional benefit in increasing decay resistance, increasing Ca 2+ into fruit and increasing levels of bioactive compounds in jujube fruit. CONCLUSION: SAEW in combination with Ca(NO3 )2 or Ca(OAc)2 has commercial potential for fresh jujube disinfection and improving storage quality as a result of the cleaning processes. © 2019 Society of Chemical Industry